Expectations and fears of working adult students in higher education at a public university in Chile - Irving Osmán Cadamuro Inostroza (Revista MENDIVE, 2023)
Students enrolled in evening continuation study programs at a higher education institution face an academic world with expectations and fears throughout their entire training process. With their different family and work responsibilities, the students who are most prepared and adapted to the new times will advance and finish their educational instruction. Others will make the decision and give up their career, throwing away the possibility of obtaining a professional degree and better job prospects. The study explored the meaning that working adult students construct, regarding the expectations and fears during the development of their study program, in the Business Administration Engineering career, at the Teaching and Linking Center of the Arturo Prat University in Santiago de Chile, in the year 2021. A qualitative methodology was used, at an exploratory level and with a design with a case approach. The information was collected through an unstructured interview via email. The processing of the information was carried out using an Excel spreadsheet. The main results showed that the highest expectations of working adult students are to improve job performance and obtain a professional degree. Regarding the main fears, they expressed the lack of time to study and the level required by the university. The most relevant conclusions were aimed at developing higher education programs, according to the academic needs of a working adult and support plans throughout the program on emotional and mental health issues.